Vocational Education and Training and its Role in the Economic Development in South Korea - ِEl Baz, Mohamed Anas Mohamed (الجمعية المصرية للاقتصاد السياسي والإحصاء والتشريع, 2016)
The main purpose of this paper is to study vocational education and training (VET) in South Korea and its role in the economic development. We’ll handle the obsession of the Koreans in education, a snapshot about vocational education and training in Korea ,its progress from until now and the role of vocational education and training on phases of economic development in Korea, beginning with pre sixties when there were the Japanese occupation , the Second World War and the Korean War in addition to the post war era till the sixties. In the sixties when the five year plans started, vocational education provided Korea with well prepared technicians and workers according to the demands of this period of light and intermediate industries. In the seventies when the third and fourth five year plans VET developed according to the demands of the period of heavy industry. In the eighties when the fifth and sixth five year plans VET progressed according to the demands of the period of heavy and petrochemical industry. Then the nineties until now, the world changed and high tech dominated and forced VET to change technological industries. Korea used VET as a core to push the economic development forwards by providing the labor market with well prepared engineers, technicians and workers.
Keywords: التدريب المهني -- التنمية الاقتصادية -- كوريا الجنوبية -- التنمية البشرية